Models of School-Based Interventions: Protocols for Crisis Situations and Recovery Courses for the Promotion of Well-Being - Cassetti, Alessandra; Mancaruso, Alessandra; Costa, Stefano (Journal of Recovery in Mental Health, 2026)
This paper presents school-based intervention models designed to promote psychological well-being and manage crisis situations, with particular focus on suicide prevention. Two complementary approaches were developed: (1) well-being promotion courses based on the Five Ways to Wellbeing, and (2) Recovery Courses inspired by the Recovery College model, adapted to high school settings. Additionally, crisis management protocols were implemented to support schools following traumatic events such as student suicide.Both models emphasize co-design, active participation of students, teachers, and parents, and peer-to-peer support. In crisis contexts, interventions are individualized, phased, and coordinated with community mental health services. The results highlight how student involvement fosters emotional expression, resilience, and a sense of connectedness. These initiatives align with the Italian National Mental Health Plan 2025–2030, which promotes recovery-oriented, integrated pathways centered on autonomy, relationships, and social participation.